Islam and Muslims in Germany - Al-Hamarneh, Ala.; Thielmann, J. (Muslim minorities ;, 2008)
In the European discourse of post 9/11 reality, concepts such as "Multiculturalism", "Integration" and "European Islam" are becoming more and more topical. The empirically- based contributions in this volume aim to reflect the variety of current Muslim social practices and life-worlds in Germany. The volume goes beyond the fragmented methods of minority case studies and the monolithic view of Muslims as portrayed by mass media to present fresh theoretical approaches and in-depth analyses of a rich mosaic of communities, cultures and social practices. Issues of politics, religion, society, economics, media, art, literature, law and gender are addressed. The result is a vibrant state-of-the-art publication of studies of real-life communities and individuals. Contributors are Kilian Bälz, Kea Eilers, Friedmann Eissler, Konrad Hirschler, Jeanette S. Jouili, Melanie Kamp, Matthias Kulinna, Judith Pies, Claudia Preckel, Robert Pütz, Mathias Rohe, Sabine Schiffer, Verena Schreiber, Christoph Schumann†, Wolfgang G. Schwanitz, Clara Seitz, Faruk Şen, Viola Shafik, Yafa Shanneik, Martin Sökefeld, Margrete Søvik, Levent Tezcan, Jörn Thielmann, Nikola Tietze and Maria Wurm. This book is also available in paperback .